The Role Of Paramedics In The Early Recognition And Management Of Chest Pain Syndromes (The Review of Diabetic Studies, 2025)
Background: Chest pain is a common emergency medical complaint with a wide diagnostic spectrum, ranging from benign causes to life-threatening acute coronary syndromes (ACS). Early recognition and management by paramedics in the prehospital setting are critical to reducing morbidity and mortality through rapid diagnosis and timely reperfusion.Methods: This review synthesizes current evidence on paramedics' roles in early chest pain recognition, including diagnostic tools such as 12-lead electrocardiography, symptom-based risk scores, and novel point-of-care biomarker testing. It evaluates prehospital interventions, reperfusion strategies, and system-level factors influencing outcomes.Results: Paramedics effectively use structured assessments and ECG interpretation to identify high-risk ACS patients, enabling early activation of catheterization labs and direct transport to PCI-capable centers. Early administration of aspirin and nitrates, coupled with emerging technologies like AI-assisted ECG interpretation and prehospital troponin testing, shorten treatment delays and improve outcomes. System disparities and training variations impact diagnostic accuracy and treatment equity. Innovative extended paramedic roles, including community-based management, are emerging.Conclusions: Paramedics play a pivotal role in the early recognition and management of chest pain syndromes, contributing to reduced ischemic times and improved patient outcomes. Standardized training, adoption of advanced diagnostic tools, and integration into regional cardiac care systems are essential to optimize prehospital chest pain care. Future research should address gaps in paramedic-specific diagnostic accuracy, technology integration, and equity in care delivery.